Socioeconomic inequality and dental caries among Thai working age population: Analysis of Thailand National Oral Health Survey - Sirinthip Amornsuradech; Warangkana Vejvithee (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to determine the relationship between socioeconomic status (SES) and oral health among Thai adults. Design/methodology/approach - This study is a cross-sectional analytical study using secondary data from the 7th Thailand National Oral Health Survey (2012). Age group 35-44 years old samples were used to represent the working age population. Oral health outcome was determined by untreated dental caries. SES was indicated by income, education and occupational groups. Demographic background, oral health-related behavior and access to dental service were adjusted for analysis. Binary logistic regression analysis was performed to determine the relationship between independent variables and oral health outcome. Findings - People with lower education showed a higher odds ratio for having untreated dental caries before and after controlling for related variables. Those living in the north and northeast, using additional cleaning tools and going to the public provider for dental service also showed better oral health. Research limitations/implications - The limitation of this study is that the cross-sectional study cannot indicate casual relationships. The national oral health survey was not designed to find relationships between factors. The access to data and measurement of SES was limited. The policy maker should emphasize on people with lower education which have a higher risk for dental caries to improve oral health in disadvantaged groups. Future research should include all related factors in the study including diet and knowledge about oral health. Moreover, oral health outcome is a long-term effect which accumulated through a lifetime. The social class might change over time and so do behaviors. Originality/value - There is socioeconomic inequality in dental caries of Thai working age population.